2016
DOI: 10.1002/jctb.5103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotreating and hydrothermal treatment of alkaline lignin as technological valorization options for future biorefinery concepts: a review

Abstract: Lignin has the potential to be a sustainable resource for producing biobased chemicals (e.g. phenols, aromatic hydrocarbons, vanillin) for multiple applications. However, given its heterogeneous and rigid structure, its efficient conversion to value‐added products remains one of the most important limiting factors for the successful viability of the biobased economy. Hydrotreating and hydrothermal treatment (including liquefaction, gasification and wet oxidation) are promising technologies that can convert lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 91 publications
(453 reference statements)
0
16
0
1
Order By: Relevance
“…The latter consumes the produced hydrogen equivalents [13]. Besides, hydrotreating and hydrothermal treatment of alkaline lignin in methanol over Ru/Al 2 O 3 have been found to improve product yield and selectivity and reduce char formation at lower working temperatures and pressures [53].…”
Section: Hydrogenolysis Of Ligninmentioning
confidence: 99%
“…The latter consumes the produced hydrogen equivalents [13]. Besides, hydrotreating and hydrothermal treatment of alkaline lignin in methanol over Ru/Al 2 O 3 have been found to improve product yield and selectivity and reduce char formation at lower working temperatures and pressures [53].…”
Section: Hydrogenolysis Of Ligninmentioning
confidence: 99%
“…Many papers have reported catalytic methods to oxidize β‐ O ‐4 linkages in lignin, making lignin more reactive for further depolymerization …”
Section: Resultsmentioning
confidence: 99%
“…The utilization of lignin has been studied for decades and many different approaches to lignin valorization have been explored. Selective depolymerization of lignin to produce well‐defined chemicals remains very challenging owing to the complex structure of lignin . Numerous studies focused on lignin depolymerization, have reported lignin catalytic cracking, hydrolysis, reductive depolymerization, and oxidative depolymerization .…”
Section: Introductionmentioning
confidence: 99%
“…1 As a major natural resource, plants have been emphasized as alternatives due to their high content of antimicrobial agents, such as alkaloids and diverse polyphenols (i.e. 6 With the emergence of biomass refining, there is an increasing interest in exploring valuable applications for this underused resource 7 and antimicrobial development is likely to be a feasible solution for this issue. 1,2 Lignin is a dominant aromatic polymer in terrestrial plants, which consists of three phenylpropane units [namely, guaiacyl (G), syringyl (S), and p-hydroxyphenyl (H) units].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite its abundance and critical role for plant resistance to microbes, lignin is typically underused because it is traditionally viewed as a waste material or a low value byproduct from pulping and bio-energy industries. 6 With the emergence of biomass refining, there is an increasing interest in exploring valuable applications for this underused resource 7 and antimicrobial development is likely to be a feasible solution for this issue.…”
Section: Introductionmentioning
confidence: 99%